THE EFFECT OF USING JIGSAW STRATEGY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMPN 1 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Asmarani Fitri; Syofia Delfi; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This pre-experimental research was aimed to find out whether or not there was a significant effect of using Jigsaw Strategy on the ability of the first year students of SMPN 1 Pekanbaru in comprehending descriptive texts. The research design was pre-experimental research with one group pre-test and post-test design. The sample was VII HN chosen by using cluster sampling technique. The data were calculated by using Microsoft Excel 2010 and analyzed by using SPSS. The result of the data analysis showed that mean scores of the pre-test was 70.27 and the mean score of the post-test was 85.29. In other words, the mean scores of the post-test was higher than the pre-test. The result also showed that the value of t-test was higher than t-table (13.880 > 2.034) at significance level of 5%. It can be concluded that Hypothesis was accepted. Thus, there was a significant effect of using Jigsaw Strategy on the ability of the first year students of SMPN 1 Pekanbaru in comprehending Descriptive Texts. Several recommendations were given for students such as study in group like Jigsaw and be more focus to increase their vocabulary. In line with it, the teachers need to gave more attention on how to improve students’ comprehension when implementing Jigsaw Strategy in the class.Key Words: Effect, Jigsaw, Strategy, Descriptive Texts.